2011
DOI: 10.2337/dc10-1490
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbohydrate Counting on Glucose Control and Quality of Life Over 24 Weeks in Adult Patients With Type 1 Diabetes on Continuous Subcutaneous Insulin Infusion

Abstract: OBJECTIVEFew studies have assessed the efficacy of carbohydrate counting in type 1 diabetes, and none have validated its efficacy in patients who are treated with continuous subcutaneous insulin infusion (CSII). The aim of our study was to test the effect of carbohydrate counting on glycemic control and quality of life in adult patients with type 1 diabetes who are receiving CSII.RESEARCH DESIGN AND METHODSSixty-one adult patients with type 1 diabetes treated with CSII were randomly assigned to either learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 16 publications
2
104
0
2
Order By: Relevance
“…There is evidence that the therapy conducted in this way is safe, improves living comfort and may have a beneficial effect on anthropometric indicators such as BMI or waist circumference [17]. Although FIT is a common, accepted and apparently optimal method of therapy, meta-analyses of previous studies show only slight differences in the degree of diabetes control among patients who calculate the amount of carbohydrates and patients who administer fixed doses of prandial insulin [17][18][19]. Differences in HbA 1c in the FIT group in relation to the control group ranged from -0.35 to -0.64%, thus indicating the need to find new algorithms for calculating prandial insulin doses.…”
Section: Carbohydrate Exchangesmentioning
confidence: 99%
“…There is evidence that the therapy conducted in this way is safe, improves living comfort and may have a beneficial effect on anthropometric indicators such as BMI or waist circumference [17]. Although FIT is a common, accepted and apparently optimal method of therapy, meta-analyses of previous studies show only slight differences in the degree of diabetes control among patients who calculate the amount of carbohydrates and patients who administer fixed doses of prandial insulin [17][18][19]. Differences in HbA 1c in the FIT group in relation to the control group ranged from -0.35 to -0.64%, thus indicating the need to find new algorithms for calculating prandial insulin doses.…”
Section: Carbohydrate Exchangesmentioning
confidence: 99%
“…d/dt 7^ 0) at the onset of the experiment (t = 0). Furthermore, we investigated a mixed case in which the remote effect of insulin x(t) was assumed in steady-state (hence the initial condition from either (18) or (19) applied), whereas EM masses were not considered steady, thus being qJ EM , q® EM extra model parameters and Eq. (20) for initial conditions becoming not applicable.…”
Section: Plasma Insulin Concentrationmentioning
confidence: 99%
“…Correspondingly, for the obtain: (18) ; 'cut-off' approach we would (19) Steady-state conditions for the masses of the EM tracer compartments can also be solved algebraically:…”
Section: Plasma Insulin Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, numerous studies have demonstrated that interventions such as MNT can help patients with T1D attain better diabetes control, although much more research is needed. 10,[16][17][18][19][20][21] There are many reasons for poor adherence to treatment recommendations for patient lifestyle education, including restrictions on reimbursement by medical insurance providers for MNT or diabetes self-management training (DSMT) sessions. There is also inadequate patient access to certified programs, especially outside of major urban areas.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 99%